Fabrication of Iron Nanowire Arrays Using Nanoporous Anodic Alumina Template - Ghaffary, T.; Ebrahimzadeh, M.; Gharahbeigi, M.M.; Shahmandi, L. (Asian Journal of Chemistry, 2012)
In this work, electropolishing combined with a two-step anodization process at moderate anodization voltages of 140 V in 0.3 M oxalic acid lead to a uniform hexagonally ordered nanoporous structures. A step-down process was used that reduced the insulating barrier layer thickness through which uniform electrodeposition could be achieved. It was demonstrated that using AC electrodeposition and the step-down process leads to uniform iron nanowire arrays. We have employed a template-assisted approach to the fabrication of arrays of iron nanowires with the possibility to design the height and diameter of the iron nanowires only by varying the parameters of the preparations conditions. The surface roughness is associated with the fluctuations in the growth rate, which is caused by fluctuations in the thickness of barrier layer. According to the SEM images, arrays of iron nanowires have ranging from 1 to 6 μm in length and 66 nm in diameter.